Periodic Determination of Physical and Physiological Responses to High Temperature Stress in cv. Narince Grapes - Topcu Altıncı, N.; Cangi, R. (South African Journal of Enology and Viticulture, 2024)
Stress is a condition that affects or even inhibits growth, development and metabolism in plants. The type of stress, duration of application and severity also affect plants significantly. In this study, the weekly responses of Narince, a wine grape variety, to high temperature stress (HTS) in in vitro conditions were followed and stress was applied in two different periods, for 12 and 18 hours at 40°C. Some growth development (viability, fresh shoot weight, dry shoot weight, number of leaves, shoot length), physiological (ion flow and relative water content (RWC)) and biochemical (malondialdehyde (MDA)) analyses were done, with weekly follow-ups after the applications. In addition, the damage was graded visually. At the end of the application of both stresses, the percentage viability rate started to decrease. This rate decreased more slowly during HTS for 12 hours, while a faster decrease was observed in HTS for 18 hours. The number of healthy plants to be evaluated could not be reached after the fourth week. Growth and development parameters – fresh shoot weight (g), dry shoot weight (g) and shoot length (mm) – decreased after both stress applications, and these values were found to be statistically significant. After 12 hours of HTS application, the highest MDA value was determined at 0.274 nmol in the sixth week, while the lowest MDA value was determined in the first week, at 0.137 nmol. After 18 hours of HTS application, the highest MDA value was determined in the fourth week, at 0.263 nmol, while the lowest MDA value of 0.103 nmol was determined in the first week.